2020
DOI: 10.3389/fimmu.2020.00154
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Investigation on Complement Pathway Activation in Diabetic Retinopathy

Abstract: The complement system plays a crucial role in retinal homeostasis. While the proteomic analysis of ocular tissues in diabetic retinopathy (DR) has shown the deposition of complement proteins, their exact role in the pathogenesis of DR is yet unclear. We performed a detailed investigation of the role of the complement system by evaluating the levels of major complement proteins including C3, C1q, C4b, Complement Factor B (CFB), and Complement Factor H (CFH) and their activated fragments from both the classical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 45 publications
(48 reference statements)
5
46
0
1
Order By: Relevance
“…Under injury or ischemic stress, they get activated, proliferate and migrate to the site of damage, while releasing pro-inflammatory cytokines and ROS to counter the damage [24]. We recently demonstrated the role of microglial mediated aberrant complement activation in the pathogenesis of DR [25]. That study showed that a gradual increase in the expression of CFH (inhibitor of alternate complement pathway) and CD11b (activated microglial marker) in the retina (at an early stage) culminated in epiretinal membranes changes in DR patients further supporting for a major role of microglia and the alternative complement pathway in disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Under injury or ischemic stress, they get activated, proliferate and migrate to the site of damage, while releasing pro-inflammatory cytokines and ROS to counter the damage [24]. We recently demonstrated the role of microglial mediated aberrant complement activation in the pathogenesis of DR [25]. That study showed that a gradual increase in the expression of CFH (inhibitor of alternate complement pathway) and CD11b (activated microglial marker) in the retina (at an early stage) culminated in epiretinal membranes changes in DR patients further supporting for a major role of microglia and the alternative complement pathway in disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Cellular and Infection Microbiology | www.frontiersin.org November 2020 | Volume 10 | Article 586946 , CRX (Fujinami-Yokokawa et al, 2020), CFI and CFB (Rathi et al, 2017;Shahulhameed et al, 2020), and KCNJ13 (Toms et al, 2019) have been linked to retinopathy. Additionally, SLC38A8 contributes to congenital nystagmus (Weiner et al, 2020), and RIMS1 and CABP4 are associated with dystrophy (Sisodiya et al, 2007) and synaptic disorder of cone-rod (Littink et al, 2009), respectively.…”
Section: Rop18-mediated Transcriptional Reprogramming Of Hek293t Cellsmentioning
confidence: 99%
“…Dysregulation of the complement system can lead to uncontrolled inflammation and retinal degeneration. Diseases such as age-related macular degeneration and diabetic retinopathy have shown evidence of altered complement homeostasis within the retina [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%